- PENGGUNAAN LAGU “AKU MAU” PADA PRODUK MAINAN BONEKA “PUTRI ANISA HIJAB PERFUMED DOLL”: - - Felicitas Citra Permatahati Nainggolan; Bustani, Simona (Reformasi Hukum Trisakti, 2024)
Copyright violations have occurred frequently over the years, with one prevalent issue being the unauthorized duplication of copyrighted works. A notable instance of this is the unauthorized use of the song "Aku Mau" in the "Putri Anisa Hijab Perfumed Doll" toy. This case examines the protection of the song "Aku Mau"'s creator in relation to the doll product and the considerations of the Commercial Court judges based on Law No. 28 of 2014 on Copyright. The research methodology used is normative legal research with a descriptive approach, drawing on secondary data to support primary data. Data was gathered through fieldwork and literature review, then analyzed qualitatively with conclusions drawn using deductive reasoning. The results of this research is that the actions by GO TOYS and PT. BINTANG CAHAYA KENCANA involved the unauthorized duplication of the song "Aku Mau" for commercial gain. The conclusion is that the judges’s decision was justified, as the DJKI copyright registration confirmed Inge Christiane as the rightful creator of the song "Aku Mau." Consequently, the Commercial Court judges ruled in favor of awarding partial material damages totaling Rp. 4,000,000,000.